Analisis manajemen operasional terhadap efisiensi biaya produksi - Ainurrohmah, Cindy (Maliki Interdisciplinary Journal, 2026)
Production cost efficiency is a crucial factor in improving a company's competitiveness and poverty reduction. Operational management plays a key role in managing production resources to ensure effective and efficient production processes. This study aims to analyze the role of operational management in production cost efficiency. The study employed a literature review method with a qualitative approach. Data were obtained from relevant articles accessible through Google Scholar and then analyzed descriptively. The study's results indicate that the implementation of effective operational management, encompassing production planning, inventory control, work scheduling, and quality control, can reduce waste, increase productivity, and lower production costs. Therefore, integrated operational management is a crucial strategy for improving production cost efficiency and a company's competitive advantage.